Pseudo Maximum Likelihood Approach for the Analysis of Multivariate Left-Censored Longitudinal Data - Solomon, Ghideon (Stat Med, 2016)
The linear mixed effects model based on a full likelihood is one of the few methods available to model longitudinal data subject to left-censoring. However, a full likelihood approach is complicated algebraically due to the large dimension of the numeric computations, and maximum likelihood estimation can be computationally prohibitive when the data are heavily censored. Moreover, for mixed models, the complexity of the computation increases as the dimension of the random effects in the model increases. We propose a method based on pseudo likelihood that simplifies the computational complexities, allows a wide class of multivariate models, and that can be used for many different data structures including settings where the level of censoring is high. The motivation for this work comes from the need for a joint model to assess the joint effect of pro-inflammatory and anti-inflammatory biomarker data on 30-day mortality status while simultaneously accounting for longitudinal left- censoring and correlation between markers in the analysis of Genetic and Inflammatory Markers for Sepsis (GenIMS) study conducted at the University of Pittsburgh. Two markers, interleukin-6 (IL-6) and interleukin-10 (IL-10) which naturally are correlated because of a shared similar biological pathways and are left-censored because of the limited sensitivity of the assays, are considered to determine if higher levels of these markers is associated with an increased risk of death after accounting for the left-censoring and their assumed correlation.